Comparison Between the Effects of Continuous and Intermittent Light-Intensity Aerobic Dance Exercise on Mood and Executive Functions in Older Adults - Hyodo, Kazuki; Suwabe, Kazuya; Yamaguchi, Daisuke; Soya, Hideaki; Arao, Takashi (Frontiers in Aging Neuroscience, 2021)
There is a growing body of evidence suggesting that one bout of moderate-intensity exercise enhances executive functions in older adults. However, in terms of safety, feasibility, and continuity, older individuals prefer light, easy, and fun exercises to moderate and stressful exercises for improving executive functions. Therefore, light-intensity aerobic dance exercise (LADE) could be suitable if it produces potential benefits related to executive functions. As for continuous vs. intermittent exercise, intermittent exercise has received a lot of attention, as it results in greater effects on mood and executive functions than continuous exercise; however, its effects in older adults remain uncertain. Thus, in this study, we aimed to examine the acute effects of intermittent LADE (I-LADE) in comparison with those of continuous LADE (C-LADE) on mood and executive functions. Fifteen healthy older adults participated in 10-min I-LADE and C-LADE conditions on separate days. Perceived enjoyment following exercise was assessed using the Physical Activity Enjoyment Scale (PACES). The pleasantness of the mood during exercise and pleasure and arousal levels after exercise were assessed using the Feeling Scale and Two-Dimensional Mood Scale, respectively. Executive function was assessed using the Stroop task before and after exercise. As a result, pleasantness of the mood during exercise and exercise enjoyment levels were greater in I-LADE than in C-LADE. Arousal and pleasure levels and Stroop task performance increased after both LADEs and did not differ between the two exercise conditions. These findings suggest that although enhancement of mood and executive functions after exercise did not differ between C-LADE and I-LADE, I-LADE could be more enjoyable and fun than C-LADE. This study will help in the development of exercise conditions that can enable the elderly to enhance their executive functions in a fun way.